Etnofarmakologi: Pengetahuan Khusus Yang Umum - Dyan Fitri Nugraha; Kunti Nastiti; Faisal Rahman (LPPM Universitas Sari Mulia, 2022)
Background: The use of traditional medicine in the community is increasing every year. Along with the development of information technology and the urgency of a pandemic, making people realize the need for traditional medicine. The development of information circulating on social media regarding the identification, efficacy, and processing of traditional medicines is not entirely correct. Objective: The high consumption and flow of information in cyberspace, especially by young people, causes the need for an analysis of the level of truth of knowledge related to traditional medicine. This is the aim of this research. Methods: Using a survey method with quantitative descriptive analysis based on online questionnaires via google form to young students (18-24 years old). The survey includes the identification, efficacy and processing of traditional medicines. Results: The average level of knowledge on identification, efficacy, and processing of traditional medicines with different levels of popularity of traditional medicines was <60%. The majority of respondents only know about traditional medicines that are commonly known, while information on the potential of other local natural resources is still not well distributed. Conclusion: The low level of respondents' knowledge of traditional medicine is a challenge for regulators, academics, and practitioners to be able to ground information about ethnopharmacology. In other words, disseminating special knowledge so that it becomes common.